Biotechnology and Biochemistry of Marine Natural Products - Baerga-Ortiz, Abel (Puerto Rico Health Sciences Journal, 2009)
Marine ecosystems are a source of biologically active compounds, many of which are currently in clinical use. With the goal of increasing the availability and the chemical diversity of these important compounds, more researchers are applying the tools of biotechnology to the discovery and production of marine natural products. This review summarizes the recent efforts towards the characterization of the biochemical pathways that result in the production of marine natural products, with an emphasis on the work aimed at understanding the enzymatic activity involved in the biosynthesis of marine natural products.